Efficacy and safety of left bundle branch area pacing versus biventricular pacing in heart failure patients with left bundle branch block: study protocol for a randomised controlled trial. Issue 9 (24th September 2020) - Cheng, Liting; Zhang, Junmeng; Wang, Zefeng; Zhou, Mengge; Liang, Zhuo; Zhao, Lin; Chen, Jieruo; Wu, Yongquan
Abstract : Introduction: Left bundle branch area pacing (LBBaP) has been accepted as a physiological pacing method that can yield narrow paced QRS waves. For patients with failed biventricular pacing (Bi-V), LBBaP is another feasible option. However, no randomised controlled study has evaluated the efficacy and safety of LBBaP in heart failure patients with left bundle branch block (LBBB). Therefore, we aimed to conduct this type of randomised controlled trial. Methods and analysis: This study is a single-centre, randomised controlled non-inferiority trial. This study will be conducted at the cardiac centre of Beijing Anzhen Hospital. From January 2020 to December 2022, 180 heart failure patients with reduced left ventricular ejection fraction (LVEF ≤35%) and LBBB undergoing Bi-V implantation will be consecutively enrolled in this study. Participants will be randomised at a 1:1 ratio into an experimental group (LBBaP) and a control group (Bi-V). The primary outcome is LVEF. The secondary outcomes are NT-proBNP, duration of the QRS complex, end systolic volume, end diastolic volume, the 6-minute walking test and quality of life (SF-36 scale), all causes of mortality, cardiovascular death, rehospitalisation rate of heart failure, other rehospitalisation rates, major complication rates, procedure costs and hospitalised dates. Ethics and dissemination: This study has been approved by the Beijing Anzhen Hospital Medical Ethics Committee (No. ks201932). The results of this study will be presented at domestic and international conferences. We hypothesise that LBBaP is non-inferior compared with Bi-V for treating patients with heart failure and LBBB. This trial will provide evidence-based recommendations for electrophysiologists. Trial registration number: Chinese Clinical Trial Registry (ChiCTR2000028726).